(untitled) (Journal of Applied Learning and Teaching, 2022)
This study critically examines the gap between policies and practices in the context of refugee education in Jordan. To understand the extent of the gap, this paper analyzes the official policies that outline the priorities of refugee education and compares these results with the perceptions of teachers of refugees with a focus on the types of curricula refugees study and the professional development programs these teachers receive. This study casts more light on this area by employing a mixed methods approach, namely, content analysis and conducting an online survey with the teachers of refugee students. This study found that the education of refugees should be reformulated in terms of appointing qualified teachers who could adapt the curriculum according to the refugee students’ levels and needs. This study revealed that there is a gap between what policymakers think and teachers’ perceptions of education. The latter highlights the importance of advancing education when strategizing future policies on refugees’ education.